Critical Study Relevance of Act No. 10 of 2016 with Government Regulation No. 151 of 2000 - Iva Amiroch (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2018)
Regional Head Elections regulated in Act No. 10 Of 2016 and Government Regulation No. 151 of 2000. So it will be described how the normative study the relationship between the Act No. 10 of 2016 by Government Regulation No. 151 of 2000 and how the relevance of critical studies law OF No. 10 of 2016 with a norm of life in society. Normatively Act 10 of 2016 is higher position with Government Regulation No. 151 of 2000, which is in line with the principle of Lex Superiori Derogat Lex inferiori, namely the rule of law higher can cancel the legal regulations below or lower, in other words lower regulation becomes invalid if it is contrary to a higher rule thereon, it is necessary synchronization between legislation No. 10 of 2016, with the Government Regulation. The problematics arise when there is a Constitutional Court decision No. 42 / PUU-XIII / 2015 annul Article 7, paragraph 2 (g) of the Act No. 10 of 2016, however, the cancellation should also be seen from the law of life in society (Living Law ).Keywords: Regional Head Election; Norms; Law.